Immunology of disorders of neuromuscular transmission. - Vincent, A (2006)
The neuromuscular junction (NMJ) is a prototype synapse and myasthenia gravis is the prototypic antibody-mediated disorder. There are now three other disorders of neuromuscular transmission caused by antibodies to other essential components of the NMJ. Antibodies to the muscle-specific kinase, MuSK, are defining a new form of myasthenia that can be associated with muscle atrophy. Antibodies to voltage-gated calcium channels are responsible for muscle weakness and autonomic dysfunction in the Lambert Eaton myasthenic syndrome. Antibodies to voltage-gated potassium channels are found in patients with a range of disorders affecting the NMJ, the autonomic system or the central nervous system. The pathogenic mechanisms probably depend on the IgG subclass of the antibodies and are only partly shared between the diseases.